The Forecasting of Electricity Consumption in the UAE Based on ARIMA Model - Balila, Abdulsalam Elnaeem; Shabri, Ani (Technium Electro, 2024)
The increase in electricity consumption in the United Arab Emirates (UAE) has become an inevitable reality, and it can be said that with the increase of the population and climate change, the consumption of electricity will increase dramatically. It is necessary to forecast the consumption of electricity in the United Arab Emirates because it plays an important role in planning strategies and policies in the future. In this study, the UAE electricity consumption data for 1985-2019 is used to forecast the electricity consumption of UAE in the future using the Auto-Regressive Integrated Moving Average model (ARIMA). The data were divided into the training data set (1985-2014) and testing data set (2015-2019) using R software to insure the model accuracy. The ARIMA model is selected to be ARIMA (0, 1, 0) to forecast the future of UAE electricity consumption. The model is adequate and accurate. The result shows that the UAE electricity consumption will continue in increasing. Electricity consumption in 2024 is expected to reach a higher level at 15,049 GWH. The results are helpful to establish effective policies, regulations, and strategies to improve and develop electricity demand management and electricity efficiency.